2021
DOI: 10.31295/ijhms.v4n1.500
|View full text |Cite
|
Sign up to set email alerts
|

Intervention with Fe supplementations and IEC about anemia against hemoglobin levels in female teenagers in state senior high school

Abstract: Iron malnutrition anemia is a micronutrient problem that often occurs throughout the world. The prevalence of nutritional anemia in the teenagers age group nationally is 18.4%. The government has a program in an effort to prevent anemia in adolescents, which is to provide one grain of iron supplements every week throughout the year for female teenagers at school. The administration was carried out for 16 weeks with details of once a week and for 10 days of menstruation, so that the total given was 52 tablets. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Many studies have shown that the dance education development at the beginning of the 21st century is characterized by the growth of students who wish to relate their lives to dance (Bigus et al, 2021;Wahyuni & Widyaningsih, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the dance education development at the beginning of the 21st century is characterized by the growth of students who wish to relate their lives to dance (Bigus et al, 2021;Wahyuni & Widyaningsih, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have revealed that the development of choreographic education at the beginning of the XXI century was characterized by an increase in the number of students who chose choreography (Bigus et al, 2021;Wahyuni & Widyaningsih, 2021). All this is achieved due to the support of dance education by universities, positive changes in the educational process related to the introduction of measures to support the development of the specialty, increase students' motivation to study choreography, using modern educational tools.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the percentage of Satisfied in turn from Q.3 to Q.12 are (12.15,13.84,14.41,17.23,9.89,10.17,14.41,18.64,9.04,12.71),and Well satisfied percentage are (14.41,5.93,5.37,4.24,9.04,8.47,13.28,16.95,3.39,3.67) respectively. Thus, it can be seen that the terms in the physical education program from Q.3 to Q.12 are still very limited (Koka & Hein, 2003;Wahyuni & Widyaningsih, 2021;Cox et al, 2008).…”
Section: Q15mentioning
confidence: 99%